PENGELOLAAN PROGRAM SATUAN PENDIDIKAN NONFORMAL DI KOTA KUPANG (STUDI KASUS DI PUSAT KEGIATAN BELAJAR MASYARAKAT OBOR TIMOR MINISTRY) - Gallex Simbolon (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
The purpose of this study was to determine the management of non-formal education unit programs in Kupang City, especially at the Obor Timur Ministry's Community Learning Activity Center (PKBM), which was seen from several aspects, namely planning, organizing, mobilizing, supervising, and evaluating. qualitative approach with case study method. The case study method is used with various considerations about a case with a more in-depth study and the conclusions are not for generalization or the conclusions of the research results cannot be applied or are limited to other cases. programs to solve various problems that exist in the community, (2) the organization of the institution provides the division of authority and duties of each division. Such as determining educators, tutors in accordance with scientific fields, (3) mobilizing there are several schedule changes in accordance with the principle of providing extra-curricular education that is more flexible than formal education program services, (4) Institutions carry out monitoring by first setting measurement standards then compare it with the reality on the ground.